Winter inoculum on the kiwifruit vines where is it hiding - Kabir, M.S.; Parry, B.E.; Bent, S.; Casonato, S.G. (New Zealand Plant Protection, 2016)
The bacterial pathogen Pseudomonas syringae pv actinidiae biovar 3 (Psa) causes significant economic losses in the kiwifruit industry This pathogen can overwinter in kiwifruit without the plant showing visible symptoms Molecular tools developed to detect this pathogen from cultures had not previously been tested at an orchard level on dormant winter vines This epidemiological study aimed to detect and quantify the inoculum present on established vines over winter targeting the areas of the scion on the pergola The experiment was conducted on female and male vines of four cultivars Actinidia chinensis var chinensis Zesy002 (commonly called Gold3) A chinensis var chinensis Zesy003 (Gold9) A chinensis var deliciosa Hayward and A chinensis var chinensis x A chinensis var deliciosa Zesh004 (Green14) Psa biovar 3 was detected on the vines of all four cultivars with quantification of the inoculum load (cfu/ml) estimated Inoculum in all four cultivars increased from winter to spring and inoculum was distributed unevenly around the cankers This research indicates Psa can be present in asymptomatic tissue suggesting management of the vines for Psa needs to occur over the winter